Estudo da produção de exopolímeros com atividade biossurfactante por microrganismos isolados do processo de compostagem de resíduos no Zoológico de São Paulo - Barros, Caroline de Almeida [UNIFESP] (2015)
The biosurfactants are compounds produced by microorganisms that increase the bioavailability of apolar compounds promotes the stabilization of oil-water emulsions.These substances are biodegradable and less toxic if compared to synthetic surfactants. Bacteria that are able to produce biosurfactants have been increasingly used in bioremediation of hydrocarbon-contaminated areas. They act by increasing the solubility of pollutants and accelerating their biodegradation. In this sense, the present study began by the isolation of 544 bacteria from the composting process that is established at the São Paulo Zoo Park Foundation (SPZPF). These isolates were screened about their surfactant abilities through the drop collapse method, emulsification index (E24) and surface tension (Du Noüy method). In this context, it was selected two bacteria, FPZSP 342 and FPZSP 84, which showed promising results regarding their abitlity to produce biosurfactant exopolymers (EPS) ratios above 1.2 g EPS / g cells, emulsification indexes (E24) above 60 % and surface tension between 30 and 40 mN/m. Through LC-MS / MS analysis using micrOTOF QII Bruker system, it was observed that both EPS produced by the selected strains, had chemical structural characteristics similar to glycolipid mixtures. These glycolipids produced by the two strains were analysed in monolayer Langmuir assays, as a form to allow note future possibility of their use in activities that aim the dispersion or petroleum emulsification. Both strains were characterized by molecular techniques based on the amplification and sequencing analysis of the 16S rDNA gene. The strain FPZSP 84 was characterized as Bacillus subtilis, while FPZSP 342 was affiliated to Staphylococcus warneri. In conclusion, we could assume that the selected bacteria in this study were able to produce biosurfactant compounds with potential for future applications in bioremediation of petroleum-impacted areas.